2018
DOI: 10.1126/sciadv.aap8652
|View full text |Cite
|
Sign up to set email alerts
|

Coherent order parameter oscillations in the ground state of the excitonic insulator Ta 2 NiSe 5

Abstract: Ultrafast spectroscopy reveals coherent oscillations of a phonon-coupled BEC of excitons in an excitonic insulator.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
143
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 147 publications
(158 citation statements)
references
References 44 publications
14
143
1
Order By: Relevance
“…While these initiatives are underway, our technique may also serve as a probe for non-equilibrium superconductivity 33,34 . With so many interesting prospects, we see a bright future for phase-resolved spectroscopy of collective modes in superconductors and beyond [35][36][37][38] . Fig.…”
Section: Discussionmentioning
confidence: 99%
“…While these initiatives are underway, our technique may also serve as a probe for non-equilibrium superconductivity 33,34 . With so many interesting prospects, we see a bright future for phase-resolved spectroscopy of collective modes in superconductors and beyond [35][36][37][38] . Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Originally discussed in the context of particle physics [2] and superconductivity [3], Higgs and Goldstone excitations were found in cold atom systems, such as superfluids [4][5][6][7][8] or supersolids [9]. Higgs and Goldstone modes are well-studied in superconductors today [10][11][12][13][14][15][16][17][18][19][20][21], and similar manifestations have recently been reported in charge density wave (CDW) systems [22][23][24], antiferromagnets [25][26][27], and excitonic insulators [28]. It has been debated whether the optical and acoustic vibrational modes of solids can be considered Higgs and Goldstone excitations of the crystal lattice [29].…”
mentioning
confidence: 96%
“…4 For the present study, we have performed the measurements of time-and angleresolved photoemission spectroscopy (TARPES) to obtain such evidence that Ta2NiSe5 is actually an excitonic insulator from its pump-fluence dependence of the photoexcitation dynamics. Whereas several time-resolved studies on Ta2NiSe5 have been reported so far [14][15][16][17] , the present study is quite unique in that we employ a pump laser with shorter pulse duration (~ 30 fs), and extreme ultra violet (XUV) laser from high harmonic generation for probe pulses. Whereas we have employed 1 kHz for the repetition rate of the laser in order to generate higher order harmonics, this makes higher pump fluence available compared to higher repetition rate with the same average power of pump pulses.…”
mentioning
confidence: 99%